A method for coupling the phase-field model based on a grand-potential formalism to thermodynamic databases. Issue 5 (October 2015) - Choudhury, Abhik; Kellner, Michael; Nestler, Britta
Highlights: A method for utilizing thermodynamic information in phase-field simulations. Extends the grand-potential formalism for modelling real alloys. Minimalistic formalism with greater computational efficiency. Microstructure simulations of example binary and ternary eutectic alloys. Abstract: In this paper we derive an approach for the effective utilization of thermodynamic data in phase-field simulations. While the most widely used methodology for multi-component alloys is following the work by Eiken et al. (2006), wherein, an extrapolative scheme is utilized in conjunction with the TQ interface for deriving the driving force for phase transformation, a corresponding simplistic method based on the formulation of a parabolic free-energy model incorporating all the thermodynamics has been laid out for binary alloys in the work by Folch and Plapp (2005). In the following, we extend this latter approach for multi-component alloys in the framework of the grand-potential formalism. The coupling is applied for the case of the binary eutectic solidification in the Cr–Ni alloy and two-phase solidification in the ternary eutectic alloy (Al–Cr–Ni). A thermodynamic justification entails the basis of the formulation and places it in context of the bigger picture of Integrated Computational Materials Engineering.